2021
DOI: 10.3389/fimmu.2021.737849
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine Can Induce T Cell Apoptosis: A Potential Immunosuppressive Agent With Anti-Cancer Effect

Abstract: Capecitabine (CAP) is now widely used in the comprehensive treatment of digestive system tumors. Some clinical observations have shown that CAP may have immunosuppressive effects, but there is still a lack of clear experimental verification. In this study, different doses of CAP were administered to normal mice by gavage. Our results confirmed that CAP did not cause myelosuppression in bone marrow tissue; CAP selectively reduced the proportion of T cells and the concentration of related pro-inflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…All animals were obtained from China National Institutes for Food and Drug Control. Male Balb/c mice aged 6–8 weeks were gavaged with metronomic doses of CAP (100 mg/kg/day) (Solarbio, Beijing, China) [ 12 , 35 ]. At days 0, 7, 14, and 21, mice ( n = 10) were sacrificed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…All animals were obtained from China National Institutes for Food and Drug Control. Male Balb/c mice aged 6–8 weeks were gavaged with metronomic doses of CAP (100 mg/kg/day) (Solarbio, Beijing, China) [ 12 , 35 ]. At days 0, 7, 14, and 21, mice ( n = 10) were sacrificed.…”
Section: Methodsmentioning
confidence: 99%
“…CAP is the first-line therapeutic drug for CRC, and some clinical studies have also confirmed that CAP, especially at the dosage used in metronomic chemotherapy (a novel type of chemotherapy featuring low dosage and uninterrupted administration), has a good effect in treating HCC [ 8 11 ]. In addition, the expression of TP in T cells has been confirmed, which lays the pharmacodynamics foundation for the conversion of CAP to 5-FU in T cells [ 12 ]. Earlier experiments showed that CAP can induce apoptosis in T cells, which confirmed this view [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations